2023
DOI: 10.3390/catal13060948
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Hollow Zeolite-Encapsulated Highly Dispersed Ultra-Fine Fe Nanoparticles as Fischer–Tropsch Catalyst for Syngas-to-Olefins

Abstract: A nano-hollow zeolite-encapsulating ultra-fine Fe nanoparticle catalyst denoted as Fe@n-hS-HT was successfully synthesized through a simple water steam treatment of the Fe@n-hS catalyst prepared by the “dissolution–recrystallization” (D-R) method. The Fe@n-hS-HT catalyst had a hierarchical porous structure and a high dispersion of Fe2O3 particles with a size of 3.4 nm. Furthermore, the results of several characterization methods, such as XRD, HAADF-STEM, and H2-TPR, further demonstrated the transformation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The catalytic performance of iron catalysts depends on their active phase, transition metal promoter, alkali promoter, and support [20][21][22][23][24]. It has been shown that FT synthesis over iron catalysts is a structure-sensitive reaction [1,[25][26][27], with the intrinsic reaction rate and product selectivity being functions of iron particle size. The promoted iron catalysts have, so far, shown one of the best performances in direct olefin synthesis from syngas.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic performance of iron catalysts depends on their active phase, transition metal promoter, alkali promoter, and support [20][21][22][23][24]. It has been shown that FT synthesis over iron catalysts is a structure-sensitive reaction [1,[25][26][27], with the intrinsic reaction rate and product selectivity being functions of iron particle size. The promoted iron catalysts have, so far, shown one of the best performances in direct olefin synthesis from syngas.…”
Section: Introductionmentioning
confidence: 99%